2018
DOI: 10.1172/jci120194
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 latent reservoir size and diversity are stable following brief treatment interruption

Abstract: ClinicalTrials.gov NCT02463227FUNDING. Funding was provided by the NIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(143 citation statements)
references
References 45 publications
17
121
0
Order By: Relevance
“…To investigate the origin of viral rebound, we compared qVOA outgrowth viruses with in vivo plasma rebound viruses using SGA. Exact matches between qVOA and rebound clones have been reported only very rarely . In these three participants, we observe intermingling between the viral sequences obtained from qVOA and plasma at viral rebound, confirming their close phylogenetic relatedness.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To investigate the origin of viral rebound, we compared qVOA outgrowth viruses with in vivo plasma rebound viruses using SGA. Exact matches between qVOA and rebound clones have been reported only very rarely . In these three participants, we observe intermingling between the viral sequences obtained from qVOA and plasma at viral rebound, confirming their close phylogenetic relatedness.…”
Section: Discussionsupporting
confidence: 69%
“…There remains quite some discussion about the value of qVOA when investigating the HIV reservoir, due to rather poor correlations with rebound sequences as described here and by others . One potential explanation is that qVOA is limited to the blood compartment and does not take into account rebound coming from other anatomical reservoirs.…”
Section: Discussionmentioning
confidence: 82%
“…Stochastic simulations (Methods) with a constant VRC01 efficacy against the mutant, indicated that the latent cell pool did not vary significantly over the durations considered (Fig. 3(a)), consistent with experiments 58 . Reactivation leading to the growth of productively infected cells carrying proviruses with the N279K mutation occurred over a duration of a few days to weeks (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Our large data set of near-full-length HIV-1 provirus sequences allowed for examination of clonal proliferation according to provirus type. Clones were identified as proviruses with identical nucleotide sequences and, if deleted, with identical deletion junctions, as has been done previously (48,58,59). Although definitive assignment of clonality requires integration site analysis, full genome sequence identity provides very strong evidence for clonality (60).…”
Section: Resultsmentioning
confidence: 99%